KINERJA APARAT KELURAHAN DALAM PELAKSANAAN PROGRAM BERAS MISKIN (RASKIN) DI KELURAHAN TANJUNG GADING KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU TAHUN 2016 - Yuni Sri Wulandari; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this study was to determine the performance of village officials in the implementation of the Poor Rice Program (Raskin) in Tanjung Gading Village, Pasir Penyu Subdistrict, Indragiri Hulu Regency in 2016 and to describe what factors influence the performance of the village officials in the implementation of the Poor Rice Program (Raskin) in Tanjung Gading Village Pasir Penyu Subdistrict, Indragiri Hulu Regency in 2016. To measure the performance of the village officials in the implementation of the Raskin program, three indicators were used, namely Effectiveness, Responsiveness and Accountability.The research method used is descriptive qualitative. The data sources include primary data that is done through interviews to the source of data sought using purposive sampling techniques. In addition to primary data is also supported by secondary data obtained from documents and documentation relating to the research theme.Based on the results of the study, it can be seen from the three focuses of this study that the performance of the Village Government in the Poor Rice Program (Raskin) is not yet optimal in Tanjung Gading Village, Pasir Penyu District, Indragiri Hulu Regency in 2016. Furthermore, factors affecting the performance of the Village officials in the implementation of the Raskin program other than internal factors and external factors.Keyword: Effectiveness, Performance, Raskin Program